Dual layer hollow fibre as main component of methane fuelled solid oxide fuel cell - Omar, Ahmad Faiq (2020)
Solid oxide fuel cell (SOFC) has been regarded as one of the most amazing technologies in energy production that could directly convert hydrocarbon fuel into electricity without reforming procedure. This study was conducted to analyse the micro-tubular solid oxide fuel cell (MT-SOFC) with different electrolyte thicknesses in terms of its performance by utilising methane (CH4) as the fuel. MT-SOFCs investigated in this work consisted of thin cathode layer, coated onto co-extruded anode/electrolyte dual-layer hollow fibre (DLHF). A DLHFs with different electrolyte thicknesses had been developed in this study by adjusting the extrusion rate upon a single-step phase inversion-based co-extrusion and co-sintering process. Uniform outer electrolyte layer from 18 to 34 µm were achieved when the extrusion rate of outer layer was increased from 1 to 5 ml min-1. The fabricated DLHFs were then cosintered at various temperatures (1350, 1400 and 1450 °C) prior to reduction process at 550 °C for 3 h. In evaluating the performance of DLHFs fuelled by CH4 gas, currentvoltage (I-V) measurement, impedance spectra, as well as stability test were performed at various temperatures ranging from 750 to 850 °C. Although the bending strength and gas-tightness properties were reduced with the decrease in electrolyte layer thickness, significant improvement in power output of the cell was achieved. Power density as high as 0.32 W cm-2 was obtained on the cell with the electrolyte layer of 18 µm in thickness, which is 20 % higher than the cell with an electrolyte layer of 34 µm, which was only 0.12 W cm-2 when operated at 850 °C. Stability test has shown that the cell with thinnest electrolyte (18 µm) can only survived for 8 h while the thickest cell (34 µm) can operate up to 15 h at 750 °C. The results show that there was a significant reduction in cell performance when CH4 was used as the fuel, due to the carbon deposition as proven by Raman spectroscopy and carbon, hydrogen, nitrogen and sulphur (CHNS) analyzer as qualitative and quantitative analyses, respectively. The study also shows that the optimum electrolyte thickness has to be around 23 to 24.5 µm in order to produce a high quality DLHF to withstand carbon deposition.